Sustainable Valorization of Used Biochar for Hexavalent Chromium Removal from Wastewater and Soil Fertility Enhancement - Anwar, Dedy; Neliyati, Neliyati; Gusniwati, Gusniwati; Jasminarni, Jasminarni; Rohman, Arif; Syarifuddin, Hutwan; Nainggolan, Ellyas Alga; Wibowo, Yudha Gusti (Universitas Diponegoro, 2025)
Environmental pollution from wastewater and soil contamination remains a critical global concern, with current treatment methods often facing limitations in scalability, cost, or environmental safety. Biochar, a carbon-rich material derived from biomass pyrolysis, has emerged as a sustainable adsorbent for heavy metals and organic pollutants. While its use in environmental remediation is well-established, the fate and reuse of spent biochar have received limited attention. This comprehensive review explores the untapped potential of used biochar, particularly for the removal of hexavalent chromium (Cr(VI)) from wastewater and its role in enhancing soil fertility. We critically analyze current practices, mechanisms of Cr(VI) removal using spent biochar, regeneration techniques, and field applications, while highlighting circular economy frameworks that promote resource efficiency. The study integrates empirical evidence from recent case studies and offers policy recommendations to support large-scale implementation. This work is the first to provide an integrative review of the reuse of spent biochar with a dual focus on wastewater treatment and soil enhancement, underpinned by a circular economy perspective. It addresses critical research gaps by evaluating regeneration techniques, post-use functionality, and practical field applications, thereby positioning spent biochar as a viable, low-cost, and eco-friendly alternative in environmental management systems.